Time dependent effects of prolonged hyperglycemia in zebrafish brain and retina - Rowe, Cassie J.; Delbridge-Perry, Mikayla; Bonan, Nicole F.; Cohen, Annastelle; Bentley, Meg; DeCicco-Skinner, Kathleen L.; Davidson, Terry; Connaughton, Victoria P. (Frontiers in Ophthalmology, 2022)
Prolonged hyperglycemia causes long-term vision complications and an increased risk of cognitive deficits. High blood sugar also confers an osmotic load/stress to cells. We assessed behavioral and neurochemical changes in zebrafish brain and retina following prolonged hyperglycemia for 4-weeks or 8-weeks. At each time point, behavior was assessed using 3-chamber choice task and optomotor response; tissue was then collected and levels of inflammatory markers, tight junction proteins, and neurotransmitters determined using Western Blots. After 4-weeks, brain levels of v-rel reticuloendotheliosis viral oncogene homolog A (avian) (RelA; NF-kB subunit), IkB kinase (IKK), and glial fibrillary acidic protein (GFAP) were significantly elevated; differences in zonula occludens-1 (ZO-1), claudin-5, glutamic acid decarboxylase (GAD), and tyrosine hydroxylase (TH) were not significant. In retina, significant differences were observed only for TH (decreased), Rel A (increased), and GFAP (increased) levels. Glucose-specific differences in initial choice latency and discrimination ratios were also observed. After 8-weeks, RelA, GAD, and TH were significantly elevated in both tissues; IKK and GFAP levels were also elevated, though not significantly. ZO-1 and claudin-5 levels osmotically decreased in retina but displayed an increasing trend in glucose-treated brains. Differences in discrimination ratio were driven by osmotic load. OMRs increased in glucose-treated fish at both ages. In vivo analysis of retinal vasculature suggested thicker vessels after 4-weeks, but thinner vessels at 8-weeks. In vitro, glucose treatment reduced formation of nodes and meshes in 3B-11 endothelial cells, suggesting a reduced ability to form a vascular network. Overall, hyperglycemia triggered a strong inflammatory response causing initial trending changes in tight junction and neuronal markers. Most differences after 4-weeks of exposure were observed in glucose-treated fish suggesting effects on glucose metabolism independent of osmotic load. After 8-weeks, the inflammatory response remained and glucose-specific effects on neurotransmitter markers were observed. Osmotic differences impacted cognitive behavior and retinal protein levels; protein levels in brain displayed glucose-driven changes. Thus, we not only observed differential sensitivities of retina and brain to glucose-insult, but also different cellular responses, suggesting hyperglycemia causes complex effects at the cellular level and/or that zebrafish are able to compensate for the continued high blood glucose levels.